If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -24 = 7x + -28 Reorder the terms: -24 + 4x = 7x + -28 Reorder the terms: -24 + 4x = -28 + 7x Solving -24 + 4x = -28 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -24 + 4x + -7x = -28 + 7x + -7x Combine like terms: 4x + -7x = -3x -24 + -3x = -28 + 7x + -7x Combine like terms: 7x + -7x = 0 -24 + -3x = -28 + 0 -24 + -3x = -28 Add '24' to each side of the equation. -24 + 24 + -3x = -28 + 24 Combine like terms: -24 + 24 = 0 0 + -3x = -28 + 24 -3x = -28 + 24 Combine like terms: -28 + 24 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333
| .2x^2-.8x+.5=0 | | 3/4d-1/5=1/6 | | 8x-45=6x+54 | | x^(1/2)/2=343^(1/3) | | x(x-6)+9=25 | | 10.2+3n=11 | | X+.05x=294000 | | 10y-7=4y+5 | | -84=-2+6x+8+3x | | -7b=63 | | 2(u-2)-5u=-2(u+3) | | 4a=2a+1 | | 4x+5x+3+5x+6=107 | | 5x-9=87-7x | | 4x+2y+3z= | | 0=14x^2+x-4 | | 2x^2+48x+160=364 | | 10(z+3)-3(z-3)=2(z-1)+4(z-4) | | 28x-7-16x=3(4x-3)+2 | | ln(x+10)-ln(x+4)=3 | | -1/5×-9/7=-3/2 | | 96-33-(-109)= | | 6=-3(22-y)+2(y-4) | | 83-(6x+15)=6(x+7)+x | | in(x+10)-in(x+4)=3 | | 5a+7y+8a+7y= | | 2x^3+5x^2+x+3=621 | | 4x+5x+2+5x+7=107 | | 2x^3+5x^2+x-618=0 | | 2x^2+17x+130=0 | | -5/8×1/4 | | f(x)=7x-8/9 |